PELATIHAN HABSYI PADA PEMUDA GUNA MENGEMBANGKAN BAKAT DAN KREATIFITAS - Delia Putri Pramudita; Muhammad Ilham Habibullah; Agung Setiawan; Muhammad Dahri; Asita Nova Ferkhory; Novia Rahmadani; Mukhlis Rohmadi (Jurnal Abdimas Bina Bangsa, 2024)
The community service carried out by IAIN Palangka Raya KKN students aims to develop the talents and creativity of teenagers in Palingkau Sejahtera Village. There is also a method used in this service, namely mentoring activities carried out by KKN students for teenagers in Palingkau Sejahtera Village. There are also research results resulting from the service during this KKN, namely that the teenagers in the Palingkau Sejahtera village who have taken part in regular regular training activities have been able to develop their talents and creativity, apart from that, they have also been able to appear in large events. in the village of Palingkau Sejahtera, namely the 10th of Muharram event, where in this event the teenagers who appeared in the event were given full appreciation by the community as well as the local village head